Viscous dissipated hybrid nanoliquid flow with Darcy–Forchheimer and forced convection over a moving thin needle - Taza Gul; Junaid ur Rahman; Muhammad Bilal; Anwar Saeed; Wajdi Alghamdi; Safyan Mukhtar; Hussam Alrabaiah; Ebenezer Bonyah (AIP Advances, 2020)
The study of hybrid nanoliquid can help achieve innumerable advanced features that make heat and mass transmission more convenient, such as in hybrid-powered engines, pharmaceutical processes, microelectronics, domestic refrigerators, engine cooling, and so on. The intention behind this work is to escalate the performance of water based hybrid nanoliquid containing magnetic ferrite and CNTs. The viscous dissipated convective flow of hybrid nanoliquid passing over a horizontal moving thin needle is scrutinized. The nonlinear structure of the differential equations is transfigured into dimensionless ordinary differential equations, making use of Karman’s scaling. The results are deciphered via manipulating the homotopy analysis method. The physical entities out-turn on velocity, concentration, and the temperature profile are sketched and discussed in brief. The numerical outcomes are the skin friction, Nusselt number, and Sherwood number. It is perceived that the design of the needle including its size and shape strongly affects the thermal characteristics and fluid velocity. The energy and flow boundary layers of both CNTs and Fe3O4 are significantly diminished with the increase in the needle size. The uses of CNT + Fe3O4/H2O are more dominant for the enactment of thermo physical characteristics of carrier fluids associated with iron oxide nanomaterials.